Effects of Cow Manure on Growth and Yield of Lettuce (Lactuca sativa L.) In salty affected soil and drip irrigation system, Bahrain kingdom - Elgubshawi, Dr. Abdelmoneim Ahmed; Hussin Attia, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
To get benefit of the   available resources (FYM), save environment and to reduce the production cost the present study is focused on the response of lettuce (Lactuca sativa L.) to the application of   caw manure. Experiment was laid in a Complete Block Design (RCBD); four rates of farm caw manure 00,8,16 and 24 tons/acre were added in the open research farm, Budaiya, Bahrain Kingdom.Plant height, head diameter (core length), number of leaf, leaf area index(LAI), marketable yield and the nutrient composition of fresh lettuce were measuredThe result indicated that lettuce grown in a sand soil amended with relatively higher amounts of organic manures (24t/acre) exhibited some good growth. Leaf area index, Avg. core length and yield (marketable yield) were significantly responded. while number of leaf and Plant height were not. In term of quality; generally, amounts of calcium, zin and iron were increased with increasing rate of organic fertilizer but the calcium content was increased significantly.Lettuce can be grown better using 24 t/acre caw manure, for higher yield and quality.Further study on even higher levels of caw manure is suggested